Pengembangan Jaringan Jalan Tol antar Kota dalam Perspektif Sistem Transportasi Berkelanjutan - Riyanto, Bambang (MEDIA KOMUNIKASI TEKNIK SIPIL, 2006)
Nowadays, the government plan to develop toll road intercity network, which connect Jakarta and Surabaya city, Either Roadway or toll road that connecting one town to another represent supporting tools towards economic activity. Lacking in road connetion services, can cause high expense economics which finally encumber society as a whole. Â In the last decade, government find difficulties to increase road connection service, either from capacities or also from its qualiaty side. Recent years, the maintenance cost allocation seems to short to fulfill the requirement standard of maintenance. Therefore the toll road constructed by private sector should be mobilize as one of the society participation form in the infrastructure development, besides reduce the monetary burden to government. It is need to learn furthermore, whether the toll road construction oppose against the principle of environment conservation. Principles of sustainable development also consider to the economics aspect. Both aspects, economic and environment have to be considered and in line together. In evaluating a big project, there are some method which could direct or indirectly calculate its cost benefit. Its should be recognized whether the toll road construction comply with the financial, economics and social aspects. In the view of economics, toll road construction investment could mobilized a big amount of money and offering many vacancies. While in economics critism which produce a high unemployment, it should stimulate the growth of economics in a broad way. Meanwhile government should not be encumbered to make such road improvement, which is very difficult to fulfill nowadays.Keywords: toll road investment, community participation, sustainable developmentPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3939[How to cite: Riyanto, B., 2006, Pengembangan Jaringan Jalan Tol antar Kota dalam Perspektif Sistem Transportasi Berkelanjutan, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 1, pp. 95-105]